A Criterion for the Existence of the Unique Periodic Solution of One-Dimensional Periodic Differential Equation. (22nd April 2021) - Hua, Ni
Abstract : In this paper, we discuss one-dimensional differential equation with ω -period. By using the fixed point theory, the existence of a periodic solution is obtained; by using the second Lyapunov method, the uniqueness and stability of the periodic solution are obtained.